ANALISIS KEUNTUNGAN KOMPARATIF USAHA BUDIDAYA IKAN AIR TAWAR DI DESA SRIKATON KECAMATAN BUAY MADANG TIMUR KABUPATEN OGAN KOMERING ULU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
The cultivation of freshwater fish in South Sumatra Regional especially East OKU District of considerable interest as evidenced by the profits of farmers is large enough so that it can meet their needs, while the time required is not too long. This study aimed to calculate the income received by farmers and Feasibility Freshwater Aquaculture in Rural Srikaton Eastern District of Buay Madang East Ulu Ogan Ogan. The research was conducted in the village of Srirkaton. The research method used in this research is the survey method used to obtain the facts in the field by using a questionnaire. The sampling method used in this research is the method of strata. Samples are taken as many as 30 farmers sample of 83 members of the population of a percentage of 36.14 percent of samples. Based on a study of Freshwater Fish Cultivation in the village Srikaton Eastern District of Buay Madang East Ulu Ogan Ogan can be deduced, aquaculture revenues largest freshwater fish business received by farmers is in Group III Patin - Mujair amounting to Rp 16,033,155 per season harvest. From the analysis of the feasibility of that received by farmers shows that the cultivation of the Group III Patin - higher Mujair feasibility of group I and II, namely with R / C of 4.66.